In vitro measurement of proton RBE: A multi-centric comparison using a harmonized setup - Olga Sokol; Anders Tobias Frederiksen; Mateusz Sitarz; Brita Singers Sørensen; Elham Santina; Christopher Smith; John-William Warmenhoven; Marie Davídková; Anna Jelínek Michaelidesová; Irina Danilová; Oldřich Zahradníček; Amélia Maia Leite; et al. (Clinical and Translational Radiation Oncology)
Background and purpose: This study presents a multi-center comparison of in vitro cell survival measurements and RBE calculations following proton irradiations conducted under harmonized experimental conditions across six European institutions participating in the INSPIRE framework. Materials and methods: V79-4 cells were irradiated using spread-out Bragg peak (SOBP) proton fields of two configurations delivering 6 and 8 Gy with widths of 6 and 4 cm, respectively. Each center adhered to a standardized protocol, utilizing the same phantom design to minimize uncertainties related to sample positioning. X-ray reference irradiations were also performed to assess cell radiosensitivity across the participating centers. Results: Despite the consistent protocol, significant inter-institutional variability was observed in the survival measurements. For both treatment plans, the largest variation was detected in the most distal points of the SOBP (coefficients of variation of 43 % and 60 % for the 6 Gy and 8 Gy plans, respectively). Kruskal-Wallis statistical test confirmed the significant differences between the centers for each of the measured position in the proton field for both SOBP configurations. Discrepancies were observed in calculated RBE data as well, albeit preserving the expected trend for the values to slightly increase towards the distal edge of the SOBP (up to 1.5 and 1.3 for the 6 Gy and 8 Gy plans, respectively). Conclusion: The results of the study highlight the minimal biological variation one could expect performing proton RBE measurements in well-aligned experimental conditions and challenges in conducting large-scale, multi-center radiobiological experiments and inter-comparisons between literature data sets.